2004
DOI: 10.1163/1568541042665278
|View full text |Cite
|
Sign up to set email alerts
|

Monoxenic culture of Pratylenchus sudanensis on carrot disks, with evidence of differences in reproductive rates between geographical isolates

Abstract: Sterile carrot disks have been used successfully for monoxenic culture of root lesion nematodes such as Pratylenchus brachyurus (Moody et al., 1973) and P. vulnus (Townson & Lear, 1982), and excised maize roots have been used to rear P. penetrans (Tiner, 1960) and P. zeae (Jordaan & De Waele, 1988). Recent reports have indicated that P. sudanensis is causing damage to yams (Dioscorea spp.) in Uganda (Mudiope, 1999;Coyne et al., 2003). Information on the biology and epidemiology of P. sudanensis is very limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…Stoffelen et al (1999) reported that P. coffeae population of Honduras which isolated from banana was the higher reproductive fitness than Ghana and Vietnam P. coffeae populations on carrot discs. Mudiope et al (2004) found that on carrot discs all the life stages of P. sudanensis Jinja isolate had lower densities than Masaka and Rakai isolates. No male was found in all P. thornei populations on carrot discs in the current study.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Stoffelen et al (1999) reported that P. coffeae population of Honduras which isolated from banana was the higher reproductive fitness than Ghana and Vietnam P. coffeae populations on carrot discs. Mudiope et al (2004) found that on carrot discs all the life stages of P. sudanensis Jinja isolate had lower densities than Masaka and Rakai isolates. No male was found in all P. thornei populations on carrot discs in the current study.…”
Section: Resultsmentioning
confidence: 83%
“…After 6-10 hours, nematodes extracted using a modified Baermann funnel method. Each repetition of P. thornei populations of nematode suspensions was reduced to 15 ml and taken in centrifuge tubes (Mudiope et al, 2004). Nematode eggs, juveniles and females counted under the light microscope at 10X magnification.…”
Section: In Vitro Reproductive Fitness Of Five Pratylenchus Thornei Populations On Carrot Discsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altı saat sonra nematodlar geliştirilmiş Baermann huni yöntemi kullanılarak ekstrakte edilmiştir. Mezurlar içerisinde elde edilen nematod süspansiyonlarının her bir tekrarı 15 ml'ye düşürülmüş ve santrifüj tüplerine alınmıştır [54]. Santrifüj tüplerinde nematodların dibe çökmesi için 4 saat beklendikten sonra üstteki sıvı atılarak 1 ml ye düşürülmüş ve dipteki kısımdan ergin+larva ışık mikroskobu altında 100X büyütmede sayılmıştır.…”
Section: Nematod Inokulumunun Hazırlanmasıunclassified
“…This technique has since been adapted and employed for the monoxenic culture of a few root-lesion nematodes (see Kagoda et al, 2010;Santos et al, 2012). However, not all species are well adapted to this technique with some requiring months to develop, such as Pratylenchus sudanensis (Mudiope et al, 2004), and others proving unsuccessful, such as Helicotylenchus multicinctus (Speijer & De Waele, 1997). In addition, differences between carrot cultivars can lead to variations in nematode multiplication, with the most suitable cultivars not always available.…”
mentioning
confidence: 99%